Laws Governing Admissibility of Forensic Evidence in India: An Analysis (International Journal of Food and Nutritional Sciences, 2022)
The researcher has attempted to assess and evaluate the various laws, that are related to the use of scientific methods and techniques in one way or another and that may be used by the investigation agencies and courts as scientific aid, whether in the form of evidence or in another way. This researcher humbly submits that he has considered all significant laws currently in force in India that are directly or indirectly related to scientific assistance, either in the form of evidence before a court of law or which are useful as corrective or curative measures, in the courts as well as out of the courts, including crime.